A comparison of lactate concentration in plasma collected from the toe, ear, and fingertip after a simulated rowing exercise. Issue 1 (1st February 2000) - Forsyth, J J; Farrally, M R
Abstract : Objective —To examine the validity of using blood taken from the toe for the assessment of plasma lactate concentration in rowers. To achieve this, values were compared with those taken from the fingertip and earlobe. Methods —Nine subjects exercised at two separate submaximum workloads on the Concept II rowing ergometer. The loads, each lasting four minutes, elicited mean (SD) heart rate responses of 160.1 (8.5) and 180.1 (5.7) beats/min, which corresponded to 76.4 (6.1)% and 91.9 (4.7)% of the estimated heart rate maximum of the subjects. Blood was simultaneously removed after the cessation of exercise by three experimenters and was analysed for plasma lactate concentration. Results —At 76.4% of estimated heart rate maximum, the mean (SD) plasma lactate concentrations sampled from the fingertip, toe, and earlobe were 6.36 (1.58), 5.81 (1.11), and 5.29 (1.24) mmol/l respectively. At 91.9% of estimated heart rate maximum, respective values were 8.81 (2.30), 8.53 (1.37), and 8.41 (2.35) mmol/l. No significant differences (p>0.05) were found between any of the sites at either work intensity. Conclusions —The toe may offer a practical alternative for assessing the concentration of lactate during rowing, having the advantage that repeated blood samples can be removed without interruption of the rowing action.